2012
DOI: 10.1063/1.3689440
|View full text |Cite
|
Sign up to set email alerts
|

Efficient algorithm of the transcorrelated method for periodic systems

Abstract: The transcorrelated (TC) method is one of the promising wave-function-based approaches for the first-principles electronic structure calculations. In this method, the many-body wave function is approximated as the Jastrow-Slater type and one-electron orbitals in the Slater determinant are optimized with a one-body self-consistent-field equation such as that in the Hartree-Fock (HF) method. Although the TC method has yielded good results for both molecules and solids, its computational cost in solid-state calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…121 Ochi et al have also shown that integrals for the kernel ∇ 1 u 12 · ∇ 1 u 13 can be efficiently computed using plane wave basis sets. 44 This kernel appears in both TC and explicitly correlated F12 theories. 44,61 In contrast to the direct evaluation of three-electron integrals using atom-centered Gaussian basis sets in GTG theory, plane wave basis sets benefit greatly from the computational efficiency of Fourier transformations and the translational invariance of the employed kernels.…”
Section: Explicitly Correlated Plane Wavesmentioning
confidence: 99%
See 4 more Smart Citations
“…121 Ochi et al have also shown that integrals for the kernel ∇ 1 u 12 · ∇ 1 u 13 can be efficiently computed using plane wave basis sets. 44 This kernel appears in both TC and explicitly correlated F12 theories. 44,61 In contrast to the direct evaluation of three-electron integrals using atom-centered Gaussian basis sets in GTG theory, plane wave basis sets benefit greatly from the computational efficiency of Fourier transformations and the translational invariance of the employed kernels.…”
Section: Explicitly Correlated Plane Wavesmentioning
confidence: 99%
“…44 This kernel appears in both TC and explicitly correlated F12 theories. 44,61 In contrast to the direct evaluation of three-electron integrals using atom-centered Gaussian basis sets in GTG theory, plane wave basis sets benefit greatly from the computational efficiency of Fourier transformations and the translational invariance of the employed kernels. Another advantage of using plane wave basis sets is that the Fourier coefficients of the correlation factor in the above expression can be easily modified to further improve the rate of convergence of the wave function expansion.…”
Section: Explicitly Correlated Plane Wavesmentioning
confidence: 99%
See 3 more Smart Citations